Prototype of Oily Water Separator (OWS) system on the ship using Outseal PLC - Rahman, Alhabibur; Ta ali (Journal of Industrial Automation and Electrical Engineering, 2024)
Maritime transportation carries high risks of marine accidents, both while underway and at anchor, impacting the safety of crew, cargo, passengers, and the marine environment. Marine pollution, particularly from shipborne liquid waste, is a global concern with IMO standards requiring that liquid waste discharge must be below 15 ppm. Currently, oil-water separation on ships is performed manually, which is prone to human error and suboptimal equipment effectiveness. This study aims to develop an oil-water separation system on ships using outseal PLC as the central control unit. The system involves determining the water quality and turbidity values before starting the separation process. The process begins with filling waste liquid into the processing tank based on turbidity sensor readings. If the turbidity meets the desired value, the process continues with transferring to the final tank and monitoring water quality using a TDS sensor. If the water quality meets the standard (<15 ppm), disposal occurs; otherwise, the separation process continues until the criteria are met. Testing reveals that the system has an average error rate of 26.93% with an accuracy of 73.07%, while the TDS sensor measurements have an average error rate of 104.76% and an accuracy of 4.76%